Disinfection efficiency for Escherichia Coli inactivation in water using low frequency ultrasonication effect of temperature, power, and volume change on inactivation - Biel, Luisa Cyd Charisse B.; Peralta, Genandrialine L. (Quezon City College of Engineering, University of the Philippines Diliman, 2007)
Waterborne outbreak of pathogenic microrganism remains a problem worldwide. The need to utilize effective water disinfection for the prevention of diseases, and most importantly pathogenic microbial inactivation, is very important. There are conventional treatments but they produce toxic, mutagenic or carcinogenic by products. Therefore, the need to find alternative methods for effective disinfection is warranted.The present study explored the application of 20-kHz ultrasonic processor for water disinfection in conjunction with the thermal effect of the process. Escherichia coli ATCC25922 was the model organism used for this research.The experiments were conducted in batch with an ultrasound probe and divided into three stages: variable temperature, variable amplitude, and variable volume. Temperature affects the ultrasonic treatment significantly by reducing the treatment time. For controlled temperature experiment, 5 log (base 10) reduction was achieved after 30 minutes of treatment, as compared to the 10minutes of contact time for experiment without temperature control. The disinfection efficiency of E. coli increased with increase in the power input, through change in amplitude, from 0.140 log kill/min at the lowest power (122 W/L) to 0.799 log kill/min at the highest power (310 W/L). Power is directly proportional to temperature; wherein, maximum temperature of 61˚C was attained utilizing power input of 310 W/L. As for the effective volume of the sample, increasing the volume reduces the concentration of the energy being dissipated in the sample which decreases the percent inactivation of the microorganism. After 30 minutes of treatment the maximum percent inactivation for 500 mL and 1000 mL are 98.30% and 97.35% respectively. Overall, there exists a synergy between ultrasound and heat, such that ultrasonic treatment increased the vulnerability of E. coli to heat.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Water -- Purification -- Disinfection; Water -- Microbiology